Gaya Bahasa dan Makna dalam Iklan Produk Glico pada Channel Youtube Glico Japan - Trahutami, S.S., M. Hum, Sri Wahyu Istana -; Trahutami, S.S., M. Hum, Sri Wahyu Istana (Vocational College of Diponegoro University, 2024)
This paper will study the comparison between of Language Style and Meaning in Glico Product Advertisements on the Glico Japan YouTube Channel.